EFEKTIVITAS PENANGKAPAN IKAN KERAPU MACAN (Epinephelus fuscoguttatus) DENGAN BUBU MENGGUNAKAN UMPAN BUATAN - Mochammad Riyanto; Ari Purbayanto; Budy Wiryawan (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2011)
The use of bait in fishing operation attached to a fishing gear has function to attract or stimulate fish, so as to increase the fishing effectiveness. Study on catching effectiveness of grouper with basket pot by using artificial bait is urgently needed. The objectives of this study were to analysis soaking time of the artificial bait that effectively to attract grouper and to measure the effectiveness of the artificial baits to catch grouper by using basket pot. The fishing experiment methods were used in this study. The use of the artificial bait in different soaking time (day and night) has not significantly different to the grouper catch. The use of natural bait (shrimp and trash fish), however was more effective than the artificial bait to catch grouper. Keywords: artificial bait, Effectiveness, Epinephelus fuscoguttatus, basket pot